Diagrams and Cuts: A Materialist Approach to Research-Creation. (April 2015) - Springgay, Stephanie; Zaliwska, Zofia
In an attempt to disrupt arts-based research methodologies that simply fold "art" into its midst, our article enters into the theoretical conversations around critical and materialist research-creation to explore the concept of diagramming as self-organized enfoldings that do not describe or instruct experience, rather they are expressed as an open process that is emergent, vital, and abstract. The purpose of our article is to unfurl a theoretical discussion about materialist diagramming through the concepts of pure edging and cutting . In laying out this theoretical framework, we simultaneously consider how we engendered the diagrammatic within a research-creation project on artist-residencies in schools to offer ways in which one can enter into such a methodology and engage with it as data-in-the-making.